2013
DOI: 10.15415/jnp.2013.11009
|View full text |Cite
|
Sign up to set email alerts
|

Partial as Well as Total Photon Interaction Effective Atomic Numbers for Some Concretes

Abstract: Photon interaction effective atomic number (Z eff) for partial as well as total photon interaction processes has been computed using logarithmic interpolation method for seven different concretes viz. (i) Ordinary, (ii) Hematite-Serpentine, (iii) Ilmenite-Limonite, (iv) Basalt-magnetite, (v) Ilmenite, (vi) Steel-scrap and (vii) Steel-magnetite concrete in the wide energy range from 10.0 keV to 100 GeV. It has been concluded that this method has an advantage over the atomic to electronic cross-section ratio met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…For practical usage, it is required to compare the HVL value of the lutetium-based glasses to some standard shielding materials. The composition and densities of the standard shielding materials were obtained from literatures [4,19]. It has been observed that the developed glass with 25% of Lu 2 O 3 content posses better shielding properties.…”
Section: Resultsmentioning
confidence: 99%
“…For practical usage, it is required to compare the HVL value of the lutetium-based glasses to some standard shielding materials. The composition and densities of the standard shielding materials were obtained from literatures [4,19]. It has been observed that the developed glass with 25% of Lu 2 O 3 content posses better shielding properties.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous part, WinXCom calculations were evidently presented. In order to make sense of given results above we compared HVL values at 0.662 and 1.250 MeV energies relating to some heavyweight concrete materials [45], commercial window glass [46] and commercial radiation shielding glasses [47] and our findings as summarized in This phenomenon improves the radiation shielding effectiveness of our glass systems. Not surprisingly, RS 360 and RS 520 products possess slightly lower HVL values against our glass samples, because higher amounts of PbO give rise to a higher density of glass system.…”
Section: Comparison Of the Present Study With Othersmentioning
confidence: 99%